Analysis of Employee Performance and Public Service Quality on Outpatient Satisfaction at Sungai Durian Health Center Sintang - Christina Margaretha Sinambela*; Ahmad Tohardi; Milwan Milwan (Universitas Syiah Kuala, 2023)
Customer satisfaction is the rating or assessment of an individual on the extent to which a product meets or exceeds their expectations (Kotler, 2018). The Servqual theory states that service quality is measured through the difference between customer expectations of the service provided and their perceptions of the actual service performance (Parasuraman, 1988). This study aims to analyze employee performance and public service quality and their impact on outpatient patient satisfaction at Puskesmas Sungai Durian Sintang. The research employs a quantitative descriptive analysis method through a survey using a questionnaire as a data collection tool. The study population consists of patients receiving outpatient care at the Outpatient Unit in Puskesmas Sungai Durian Sintang. The research sample consisted of 100 outpatient patients randomly selected using random sampling. Data collected is analyzed through descriptive analysis, multiple linear regression technique, and T-test using SPSS 29.0 software. Data collection utilizes a Likert scale ranging from 1 to 3. Research findings reveal that employee performance is assessed at a good level, with an average score ranging from 2.61 to 2.69. The quality of public service also garners positive assessments, with an average score ranging from 2.53 to 2.67. Patient satisfaction is similarly deemed good, with an average score ranging from 2.61 to 2.69. The regression coefficient for employee performance (X1) is 0.158, indicating that each unit increase in employee performance (X1) results in a 0.158 increase in patient satisfaction (Y). On the other hand, the regression coefficient for service quality (X2) is 0.353, signifying that each unit increase in service quality (X2) leads to a 0.353 increase in patient satisfaction (Y). -value for employee performance is 0.046, while for public service quality it is 0.001. Both of these p-values are less than the established significance level (α) of 0.05. Therefore, it can be concluded that employee performance and public service quality have a significant relationship with patient satisfaction (Y) at the 0.05 significance level. Practical implications for Puskesmas management involve enhancing employee performance and public service quality to improve patient satisfaction. Puskesmas management is recommended to regularly evaluate employee performance and provide constructive feedback to aid employees in enhancing their performance. Identifying issues during the service process, implementing effective and efficient improvement efforts through employee training and development, and enhancing facilities and infrastructure in Puskesmas are also essential steps.